2021
DOI: 10.3390/oral1020013
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Bitter-Taste Receptor Genotypes, Oral Health, and Markers of Oral Inflammation

Abstract: (1) Background: The aetiology of oral disease is multifactorial, involving genetic and environmental factors, including dietary ones. Bitter taste genetics may be related to oral health through dietary modulation or non-gustatory roles, including modulation of inflammation. Investigations of bitter taste and oral health associations to date have been restricted to specific polymorphisms, limited outcomes (caries), and age-groups (children), and links to inflammation remain to be elucidated. (2) Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Many studies have reported a link between taste receptor gene polymorphisms and dental caries risk. 5 , 6 , 22 , 38 , 39 However, the majority of these studies focused only on TAS2R38 and/or TAS1R2/3 . In this study, genes involved in basic taste modalities, carbonation, and candidate fat receptors were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported a link between taste receptor gene polymorphisms and dental caries risk. 5 , 6 , 22 , 38 , 39 However, the majority of these studies focused only on TAS2R38 and/or TAS1R2/3 . In this study, genes involved in basic taste modalities, carbonation, and candidate fat receptors were assessed.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Here, no significant associations between TAS2R38 and dental caries in children were identified, which supports the findings from a recent cross-sectional study ( N = 65). 39 However, a negative correlation between TAS2R38 rs1726866 and Candida albicans (Adj. p = 0.026) was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis is also associated with an increasing cancer mortality 14 . Diabetes, rheumatoid arthritis and some other chronic diseases are also closely related to periodontitis 15 . As for the aetiology of the oral diseases, various aspects are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries have hereditary characteristics and genetic associations. Early studies have shown that: The presence of the major allele for TAS2R4-rs2234001 and TAS2R9-rs3741845 was associated with lower means, tumor necrosis factor alpha (TNF-α), interleukin one beta (IL-1β), carious, missing, and filled teeth (DMFT) index, and have 5 times more carious, missing, and filled teeth [DMFT/DMFS (carious, missing, and filled surfaces)] than those with other variations of this gene and the likelihood of missing teeth [17], [18]. Based on the risk assessment results, individual prevention programs are prepared for each patient.…”
mentioning
confidence: 99%